Modification of graphene oxide and its effect on properties of natural rubber/graphene oxide nanocomposites - Thuong, Nghiem Thi; Quang, Le Dinh; Cuong, Vu Quoc; Ha, Cao Hong; Lam, Nguyen Ba; Kawahara, Seiichi (Beilstein Journal of Nanotechnology, 2024)
Modification of graphene oxide (GO) by vinyltriethoxysilane (VTES) was investigated to study the effect of silanized GO on radical graft copolymerization of GO onto deproteinized natural rubber (DPNR). The modified GO, GO-VTES (a and b), was characterized by X-ray diffraction (XRD), Fourier-transform infrared spectroscopy, contact angle, thermal gravimetric analysis, and scanning electron microscopy. The XRD results showed the appearance of an amorphous region of silica particles at a diffraction angle of 22°. The formation of silica was investigated by 29Si NMR, and it was found that the hydrolysis and condensation of VTES proceed more completely in basic conditions than in acidic conditions. The silica content of GO-VTES(b) was 43%, which is higher than that of GO-VTES(a) (8%). Morphology of silica was observed by SEM. The DPNR/GO-VTES nanocomposites prepared with the same amount of GO, GO-VTES(a), and GO-VTES(b) were characterized with tensile tests and dynamic mechanical tests. The stress at break of DPNR/GO-VTES(a) and DPNR/GO-VTES(b) was 5.2 MPa and 4.3 MPa, respectively, which were lower than that of DPNR/GO. However, it exhibited higher stress at small strains and higher storage modulus than DPNR/GO.
Keywords: graft copolymerization; graphene oxide; natural rubber; vinyltriethoxysilane